INCLUSION OF β – MANNANASE IN CHICKEN DIETS (International Seven Journal of Multidisciplinary, 2025)
In Brazil, commercial broiler feeds consist primarily of energy and protein, exemplified by cracked corn and soybean meal, respectively. Although considered excellent quality due to their high digestibility, these ingredients contain antinutritional factors that negatively impact animal performance, such as the presence of Non-Starch Polysaccharides (NSPs). Therefore, the industry, in its constant evolution, develops alternatives capable of improving the animals' utilization of these ingredients, such as supplementing diets with exogenous enzymes. β-mannanase is responsible for hydrolyzing β-mannans, components found in soybean hulls and meal, and thus helps reduce intestinal viscosity, favoring increased digestibility and utilization of dietary nutrients. Despite numerous results regarding the inclusion of β-mannanase on zootechnical performance parameters in broilers, such as feed conversion (FCR), weight gain (WG), and feed intake (FI), few studies have elucidated its effects on amino acid digestibility. Therefore, it is concluded that there is a need for further studies to clarify the impacts of β-mannanase on this specific aspect.